2008
DOI: 10.1002/ajmg.b.30770
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between DRD3 gene polymorphism and response to clozapine in Turkish schizoprenia patients

Abstract: It is hypothesized that molecular components of dopaminergic system, especially the dopamine D3 receptor gene (DRD3), may play a crucial role in the pathophysiology of schizophrenia, because it is abundant in the limbic system of the brain and it binds antipsychotic drugs. Several groups attempted to find an association between a serine-to-glycine polymorphism of the DRD3 gene (Ser9Gly) and schizophrenia; however, the results were inconsistent. In this study, we aimed to investigate the relationship of the Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 45 publications
0
12
0
3
Order By: Relevance
“…99 Two studies analyzed the Ser9Gly polymorphism in DRD3, and the Ser/Ser genotype was found to be more frequent among non-responders to clozapine, 27,28 but other studies failed to replicate these findings. [100][101][102][103][104][105][106] The importance of Ser9Gly was confirmed in a meta-analysis, where significant differences were found when the DRD3 Ser9 allele or the Ser/Ser genotype were compared between responders and non-responders to clozapine in a sample of 233 schizophrenia patients. 107 However, a more recent meta-analysis with a much larger sample size (n=758) reported a negative but consistent trend for the DRD3 Ser9 allele and poor clozapine response.…”
Section: -98mentioning
confidence: 81%
“…99 Two studies analyzed the Ser9Gly polymorphism in DRD3, and the Ser/Ser genotype was found to be more frequent among non-responders to clozapine, 27,28 but other studies failed to replicate these findings. [100][101][102][103][104][105][106] The importance of Ser9Gly was confirmed in a meta-analysis, where significant differences were found when the DRD3 Ser9 allele or the Ser/Ser genotype were compared between responders and non-responders to clozapine in a sample of 233 schizophrenia patients. 107 However, a more recent meta-analysis with a much larger sample size (n=758) reported a negative but consistent trend for the DRD3 Ser9 allele and poor clozapine response.…”
Section: -98mentioning
confidence: 81%
“…Several studies have examined the association between this polymorphism and efficacy (227, 238, 250, 284, 316, 334, 339, 400, 418, 420, 439, 446, 449) and adverse effects like TD (211, 215, 223, 228, 237, 242, 244, 252, 257, 278, 286, 375, 401, 416, 443, 452, 473, 492). A mega-analysis of combined data from several studies on 780 patients (276) suggested the Gly9 allele conferred a small, but significant, increase in risk of TD.…”
Section: Antipsychoticsmentioning
confidence: 99%
“…A computer search on the United States National Library of Medicine and National Institutes of Health online search engine database, PubMed, was performed in order to identify all papers published up to 15 October 2009 on association studies related to the DRD3 Ser9Gly polymorphism and CLZ response. Six studies were identified: Shaikh et al, 57 Gaitonde et al, 58 Malhotra et al, 59 Scharfetter et al, 60 Arranz et al 61 and Barlas et al 62 However, Ser9Gly genotype data for Gaitonde et al 58 and Arranz et al 61 were not available from their respective publications. These data were obtained directly from the authors.…”
Section: )mentioning
confidence: 99%